Analisis Laptop Terpopuler di Indonesia Pada Februari Tahun 2023 - Jahwati, bintang (PT. ZIVANA CENDEKIAWAN BANGSA, 2025)
The laptop industry is currently experiencing very stiff competition. Not just one laptop manufacturer dominates the market. Each manufacturer displays not only its functional advantages but also brand advantages. This study aims to analyze consumer preferences for laptops in Indonesia in 2023. The data used was obtained from the sales and popularity of various laptop brands available in the market. The data analysis method used includes descriptive statistical processing to identify brands and specifications that are most in demand by consumers. The results of the study show that in 2023, laptops with high specifications and affordable prices dominate the market. Brands such as Asus and Aser are the main favorites. This research also reveals an increasing trend in the use of laptops for professional purposes and entertainment at home. The implication of this finding is the importance of laptop manufacturers to continue to develop products with specifications that meet the needs of the rapidly growing market in Indonesia. This study can be a guide for companies in designing marketing strategies and product development in the future.